Condensation of acetylacetone with amines - A. A. Jassim; A. E. Kuznetsov (Тонкие химические технологии, 2006)
Condensation of acetylacetone with diamines had been given products, which can be used to form complexes with salts of various metals, including the cobalt, as potential anticarcinogenic activity. The structure of acetylacetone with 1,6-hexamethylenediamine has been studied by X-ray